Poor sleep pattern is associated with metabolic disorder during transition from adolescence to adulthood - Zhang, Dan; Yang, Yajuan; Zhai, Shuang; Qu, Yang; Li, Tingting; Xie, Yang; Tao, Shuman; Zou, Liwei; Tao, Fangbiao; Wu, Xiaoyan (Frontiers in Endocrinology, 2023)
Objective The purpose of this study was to investigate whether sleep pattern is associated with metabolic disorder among young adults. Methods We measured sleep pattern using multiple sleep behaviors in an ongoing prospective cohort among college students (n = 1 151). At baseline, 729 college students provided fasting blood samples and human body morphological measurements for quantification of metabolic parameters. And then, 340 participants continued to take metabolic parameters measurements at two-year follow-up. Sleep patterns were defined by chronotype, sleep duration, insomnia, snoring, and daytime sleepiness. Metabolic scores was derived for 4 metabolic parameters including body mass index (BMI), waist circumference (WC), fasting blood sugar (FBG) and insulin. Multivariate linear regression model was applied to analyze the association between sleep pattern types and metabolic parameters and metabolic scores. Results In baseline survey, we found that a total of 41 (4.1%) participants had poor sleep patterns. Then, metabolic score were significantly higher among college students with poor sleep pattern, compared with those who with healthy sleep pattern at baseline (1.00 ± 0.96 vs. 0.78 ± 0.72, P <0.05 ) and two-year follow up (0.34 ± 0.65 vs. 1.50 ± 1.64, P <0.05). After adjusted for covariates, poor sleep pattern (β: 0.22, 95%CI: 0.06~2.53, P = 0.001) was associated with elevated metabolic score at two-year follow up. Conclusions Elevated metabolic burden observed in college students with poor sleep pattern highlights the need to identify and address sleep problems in order to minimize the long-term impact on disease vulnerability.